Implementation of Activity-Based Costing In Calculation of Cost of Production: Participatory Action Research - Nur Izza, Virda; Nurika Restuningdiah; Dodik Juliardi (Brilliant International Journal Of Management And Tourism, 2022)
Companies must have a more competitive advantage than other companies. To maintain its competitiveness, an effective pricing strategy is needed. Companies can set the selling price appropriately if the company can calculate the cost of the product. The cost of production can be calculated using Activity-Based Costing (ABC). ABC is a method used by manufacturing and service companies in measuring the cost of activities, resources, and cost objects. One of the SMEs engaged in the manufacturing sector is the Tanggulangin bag and luggage craft in Sidoarjo Regency which has now become a tourist icon in Sidoarjo Regency because it has good quality with a wide variety of products (Business UKM, 2010). With the development of small and medium-scale businesses, it is hoped that they will be able to absorb labor and improve the economy of the people of the Sidoarjo Regency. This study uses a qualitative approach. While the type of research used is Participatory Action Research. The results of this study indicate that the Activity Based Costing system improves the accuracy of product costing by recognizing that many of the fixed overhead costs vary proportionally with changes other than production volume. By understanding what causes these costs to increase or decrease, these costs can be traced to the individual products. This causal relationship allows the owner to improve the accuracy of product costing, which significantly improves decision-making. The application of Activity Based Costing is not only useful for its purpose of pricing but can also be used to improve the way things work. Success in implementing an Activity Based Costing system is not only by understanding the technical details but requires support from the owner and also the employees concerned to work together and take the initiative to implement an Activity Based Costing system.